Crude oil footprint in the rapidly changing world and implications from their income and price elasticities. (October 2022) - Zheng, Xinzhu; Wang, Ranran; Liddle, Brantley; Wen, Yuli; Lin, Lu; Wang, Lining
Abstract: Oil demand's income and price elasticities are important behavioral parameters for policy making. Despite its popularity in research, few studies investigated the elasticities of consumption-based oil demand, i.e., the amount of crude oil required to meet a nation's final demand regardless of the location of extractions, namely the oil footprint. Here we quantified the oil footprint of 49 countries/regions from 1995 to 2017 and estimated the elasticities of oil footprints using the panel Autoregressive Distributed Lag model. The results reveal the oil connections among countries hidden in the non-oil trade: the United States, China, and Japan imported a large amount of virtual oil embodied in the commodities and services, while Canada and Russia are the dominant suppliers. The elasticity estimations on 30 OECD countries show that oil footprints are more responsive to income increases in the long run than their short-run counterpart, with the elasticities around 0.75 and 0.48, respectively. Tariffs on oil products might not curb the oil footprint as the price elasticities are not robustly significant or negative. Moreover, the divergent elasticities of oil footprint by consumption categories highlight that more attention should be paid to the surge of oil demand embodied in construction, manufactured products, and services. Highlights: The paper quantifies the oil footprint of 49 countries/regions during 1995–2017. Income and price elasticities of oil footprint are estimated using the ARDL model. The embodied oil connections among countries beneath the apparent trade are revealed. Controlling time trend or not determines whether oil footprints decouple from income. More mitigation efforts should be put on the emissions related to non-fuel oil use.